The Second Polar Year, 1932–33 - Simpson, G. C. (Polar Record, 1931)
In the last number of The Polar Record I gave a short account of the plans for a Second Polar Year. A great deal of organizing work has been put into the scheme and Dr la Cour, the President of the International Commission for the Polar Year 1932–33, has devoted practically the whole of his time to the project.